Integração das Normas GRI e da ABNT PR 2030 na elaboração de relatórios de sustentabilidade do setor sucroenergético - Fiori, Letícia de Almeida (Universidade Federal de São Carlos, 2025)
The study analyzes the process of preparing sustainability reports in the sugarcane-bioenergy sector in the state of São Paulo, taking as reference the Global Reporting Initiative (GRI) standards and the ABNT PR 2030 guidelines, with an emphasis on the incorporation of environmental, social, and governance (ESG) practices by sugarcane producers in São Paulo. Using a qualitative approach, based on bibliographic and documentary review, the research aims to propose guidelines and a technical support model that assists producers of different sizes in the adoption, management, and reporting of sustainable practices, contributing to greater transparency and alignment with contemporary demands for socio-environmental responsibility in agribusiness. To structure the proposal, analytical and strategic management tools are employed, such as the materiality matrix for identifying priority themes; SWOT analysis for evaluating internal and external conditions related to ESG implementation; the Business Model Canvas for organizing the business model of SustentaAgro Consultoria; and OKRs and KPIs for defining, monitoring, and measuring goals and performance indicators. The results show that, although large organizations in the sugarcane-bioenergy sector have advanced in sustainability reporting, small and medium-sized producers still face significant limitations, mainly related to the scarcity of financial resources, lack of technical training, and difficulty in interpreting international norms and standards. It is concluded that the proposed model contributes to making the reporting process more accessible and applicable to the rural context, strengthening sustainable management practices and reducing the risks of greenwashing. It is recommended that future research empirically validate the applicability of the model and deepen analyses on the economic viability and impact of ESG practices in the agricultural sector.
Integration of GRI Standards and ABNT PR 2030 in the preparation of sustainability reports for the sugarcane-bioenergy sector
Keywords: ESG; Transparência; Governança; Consultoria; Produtores rurais; Transparency; Governance; Consultancy; Farmers; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS; 12. Consumo e Produção Responsáveis